Galactomannan testing and Aspergillus PCR in same-day bronchoalveolar lavage and blood samples for diagnosis of invasive aspergillosis - Eigl, Susanne; Spiess, Birgit; Reinwald, Mark; Buchheidt, Dieter; Boch, Tobias (Medical mycology, 2016)
In recent years galactomannan antigen testing (GM) and also Aspergillus PCR have become increasingly important for diagnosis of invasive aspergillosis (IA). Whether or not these tests need to be performed with bronchoalveolar lavage fluid (BALF; i.e., primary site of infection), or testing of blood samples is sufficient, remains, however, a matter of debate. We evaluated the diagnostic performance of GM ELISA, and Aspergillus PCR by using BALF samples and blood samples obtained at the same day from a total of 53 immunocompromised patients (16 with probable/proven IA and 37 with no evidence of IA according to the revised EORTC/MSG criteria; 38 patients with hematological malignancies were prospectively enrolled at the Medical University of Graz, Austria, 15 patients with mixed underlying diseases at the Mannheim University Hospital). Patients with possible IA were excluded from this analysis. A total of 34/53 (64%) of all patients and 12/16 (75%) of patients with probable/proven IA received mold-active antifungal prophylaxis/therapy at the time of the BALF procedure. Sensitivities of GM and Aspergillus PCR were 38% and 44% in BALF, and 31% and 0% in blood, respectively. Best sensitivity (75%) for detecting proven/probable IA was achieved when BALF Aspergillus PCR, BALF GM (>1.0 ODI), BALF-culture and serum-GM (>0.5 ODI) were combined (specificity 95%). In conclusion, sensitivities of the evaluated diagnostic tests - when interpreted on their own - were low in BALF and even lower in blood, sensitivities increased markedly when diagnostic tests were combined.